Climatic control of denudation in the deglaciated landscape of the Washington Cascades - Moon,S; Page,Chamberlain C; Blisniuk,K; Levine,N; Rood,DH; Hilley,GE (Nature Geoscience, 2011)
Since the Last Glacial Maximum, the extent of glaciers in many mountainous regions has declined, and erosion driven by glacial processes has been supplanted by fluvial incision and mass wasting processes. This shift in the drivers of erosion is thought to have altered the rate and pattern of denudation of these landscapes. The Washington Cascades Mountains in the northwestern USA still bear the topographic imprint of Pleistocene glaciations, and are affected by large variations in precipitation, making them an ideal setting to assess the relative controls of denudation. Here we show that denudation rates over the past millennia, as determined by 10 Be exposure ages, range from 0.08 to 0.57 yr-1, about four times higher than the rates inferred for million-year timescales. We find that the millennial timescale denudation rates increase linearly with modern precipitation rates. Based on our landscape analyses, we suggest that this relationship arises because intense precipitation triggers landslides, particularly on slopes that have been steepened by glacial erosion before or during the Last Glacial Maximum. We conclude that the high modern interglacial denudation rates we observe in the Washington Cascades are driven by a disequilibrium between the inherited topography and the current spatial distribution of erosional processes that makes this range particularly sensitive to spatial variations in climate. © 2011 Macmillan Publishers Limited. All rights reserved.